Tradisi Surang Naiak Surang Turun Ditinjau dari Perspektif Hukum Islam di Nagari Kapau Alam Pauh Duo Kecamatan Pauh Duo Kabupaten Solok Selatan - Anggun Padila; Nofiardi Nofiardi (AHKAM, 2026)
The surang naiak surang turun tradition in the implementation of Minangkabau traditional marriage has received attention in several studies, but research that specifically discusses its impact on family resilience and examines it from the perspective of Islamic law remains limited. This study aims to analyze the implementation of the surang naiak surang turun tradition in Nagari Kapau Alam Pauh Duo, Pauh Duo Subdistrict, South Solok Regency, identify its impact on family resilience, and examine it from the perspective of Islamic law. This study employed a qualitative approach with a case study design. The research participants included traditional leaders, religious leaders, couples who practiced the tradition, and local community members, who were selected through purposive sampling. Data were collected through observation, interviews, and documentation and were then analyzed descriptively and qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the surang naiak surang turun tradition is still maintained by the community as a cultural heritage that contains social and economic values. This tradition is considered capable of reducing walimah costs, strengthening kinship relations, and reinforcing social solidarity within the community. Nevertheless, this study also found the existence of social stigma and community beliefs regarding the possibility of mudharat if the tradition is not carried out. These findings contribute to the development of Islamic legal studies based on local culture, particularly in understanding the concept of ‘urf within Minangkabau society. The conclusion of this study affirms the importance of preserving local traditions that contain public benefit as long as they do not conflict with the principles of Islamic law.